2022
DOI: 10.3389/fpsyg.2022.938426
|View full text |Cite
|
Sign up to set email alerts
|

The influence of “small private online course + flipped classroom” teaching on physical education students’ learning motivation from the perspective of self-determination theory

Abstract: ObjectiveThe study aimed to enhance the learning motivation of college physical education students and improve their learning outcomes. Based on the perspective of the self-determination theory, this study explores the influence of “Small Private Online Course (SPOC) + flipped classroom” teaching on the learning motivation of students majoring in physical education and profoundly analyzes the influencing factors and promotion paths of learning motivation using this model.Materials and methodsA total of four cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The process of self-study before class prolonged the study duration and thus promoted the whole study efficiency. Likewise, Hu et al 14 investigated the influence and effect on “SPOC + flipped classroom” on physical education students’ learning motivation and found that it had a positive impact of the video lectures on student’s motivation on basketball skills and promoted their motivation autonomy. The conception of SPOC claimed for independent study.…”
Section: Discussionmentioning
confidence: 99%
“…The process of self-study before class prolonged the study duration and thus promoted the whole study efficiency. Likewise, Hu et al 14 investigated the influence and effect on “SPOC + flipped classroom” on physical education students’ learning motivation and found that it had a positive impact of the video lectures on student’s motivation on basketball skills and promoted their motivation autonomy. The conception of SPOC claimed for independent study.…”
Section: Discussionmentioning
confidence: 99%
“…The flipped classroom teaching model has become a favored approach in the field of education. It has been demonstrated that compared to the traditional classroom teaching mode, the "MOOC+ flipped Classroom" teaching mode is innovative in terms of teaching philosophy, teaching resources, and teaching methods [47].In addition, "SPOC + flipped classroom" teaching enables students to obtain more demand satisfaction by giving them more demand support, while demand support and demand satisfaction can promote the internalization of learning motivation so that students can maintain high autonomy motivation [48].These patterns promote the advancement of educational informatization and further facilitates the realization of educational modernization.…”
Section: Discussion On "Teaching Literacy" Index and Its Subordinate ...mentioning
confidence: 99%
“…This instructional design is divided into before class knowledge transfer stage, in class knowledge internalization stage, and after class knowledge consolidation stage ( Figure 1 ). Mainly from the perspective of teachers and students, the three stages of teaching activities are elaborated and analyzed in detail so that students can achieve the stage goals of knowledge construction, skill consolidation, and high-level application ( Hu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%